An Analysis of Bushra Rehman’s Novelts - Fozia Jabeen; Dr.Zamurrad Kausar; Dr.Sadaf Naqvi (Zaban-o-Adab, 2021)
"Bushra Rehman is a multi-dimensional literary entity. She has established an integral identity in the prose of short story including novel, Novelet, short story & script writing. Bushra is sentimental writer. She has observed life with deep sight. Reclamation style is prominent in Bushra Rehman's Novelets. Besides this, her novelets seem to have coalition of old & modern civilization. Bushra's novelets contain miscellaneous topics. She has been acclaimed of carnality & circumstantiality writing."